Solid Waste Management System Analysis (Case Study Bangkinang City Subdistrict) - Andrian, Wilki; Adeswastoto, Hanantatur; Tanjung, Lailatul Syifa (Journal of Engineering Science and Technology Management, 2026)
Waste management is a crucial issue in sustainable development, particularly in areas with high population growth and economic activity. This study aims to evaluate the waste management system in Bangkinang Kota District, Kampar Regency, which faces various challenges, including inadequate infrastructure, low public awareness, and a suboptimal management system. The research method used is a Mixed Method approach, combining quantitative and qualitative data collection techniques simultaneously in one study. The results indicate that the waste management system in Bangkinang Kota is still not effectively integrated, particularly in operational techniques, community participation, and institutional aspects. The lack of storage facilities, unscheduled transportation, and the habit of littering are the main challenges. Recommendations from this study include improving waste infrastructure, providing ongoing community education, and strengthening regulations and coordination between relevant parties to create a sustainable and community-based waste management system.